2018
DOI: 10.1002/jbm.b.34127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and in vitro degradation behavior of magnesium‐bioactive glass composites prepared by SPS for biomedical applications

Abstract: In order to make magnesium (Mg) a successful candidate for fracture fixation devices, it is imperative to control the corrosion rate and enhance its elastic modulus. In the present work, we have prepared bioactive glass (BG) reinforced magnesium composite using spark plasma sintering (SPS). Simultaneous application of heat and pressure during SPS decreased the softening point of BG (600°C), allowing it to coat the Mg particles partially. As a result, BG was found along the Mg particle boundaries, which was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…It was found that when the chloride concentration in the corrosion environment rose, magnesium hydroxide started to be converted into highly soluble magnesium chloride and severe corrosion occurred on the substrate [ 34 ]. On the third day, a dense white product appeared on one side of the sample, along with the development of shallow pits, as shown in Figure 3e .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that when the chloride concentration in the corrosion environment rose, magnesium hydroxide started to be converted into highly soluble magnesium chloride and severe corrosion occurred on the substrate [ 34 ]. On the third day, a dense white product appeared on one side of the sample, along with the development of shallow pits, as shown in Figure 3e .…”
Section: Resultsmentioning
confidence: 99%
“…A schematic representation of the design philosophy is shown in Figure . Hydroxyapatite (HAP), tricalcium phosphate (TCP), bioactive glasses, etc.…”
Section: Design Philosophy Of Composite Developmentmentioning
confidence: 99%
“…Schematic representation of difference between Mg/nondegradable reinforced composite and Mg/degradable bioactive reinforced composite for orthopedic applications. Reproduced with permission from ref . Copyright 2018 John Wiley & Sons.…”
Section: Design Philosophy Of Composite Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Mg alloys and BGs exhibit different degradation behaviors. BG particles can even be used to reinforce Mg alloys leading to a degradable but corrosion resistant composite [42]. As the exchange of CaO against MgO in BGs leads to a lower reactivity a controlled degradation behavior is expected [36] and should thus prevent intolerable rates of Mg 2+ -ion liberation.…”
Section: Discussionmentioning
confidence: 99%